Linearity Testing Against a Fuzzy Rule-based Model - José Luis Aznarte; Marcelo C. Medeiros; José Manoel Benítez Sánchez (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2010)
In this paper, we introduce a linearity test for fuzzy rule-based models in the framework of time series modeling. To do so, we explore a family of statistical models, the regime switching autoregressive models, and the relations that link them to the fuzzy rule-based models. From these relations, we derive a Lagrange Multiplier linearity test and some properties of the maximum likelihood estimator needed for it. Finally, an empirical study of the goodness of the test is presented.
Keywords: 330; fuzzy rule-based models; time series; linearity test; statistical inference; Fuzzy-Set-Theorie; Zeitreihenanalyse